(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to identify the role of the independent variable (car insurance) in the dependent variable (compensations granted) in the Iraqi General Insurance Company as a place for application, as well as identifying the number of traffic accidents and how car insurance can contribute to reducing or reducing them, and accordingly it was determined The research problem is the main question to identify the role that car insurance plays in reducing the amount of compensation granted by the researched company. The descriptive analytical approach was adopted, relying on the financial data and reports of the researched company for the period (2018-2022) in order to study and analyze the data to identify the premiums paid. For car insurance, the number of traffic accidents and the size of compensation, the research concluded a set of results, the most important of which is the role that car insurance plays in reducing traffic accidents and reducing the amount of compensation. The more the researched company is able to increase the public’s awareness of the demand for car insurance, the more this will lead to a reduction in car insurance rates. Accidents they may be exposed to.